GOOD GOVERNANCE DALAM PENGELOLAAN DANA DESA TELUK MAJELIS KABUPATEN TANJUNG JABUNG TIMUR PROVINSI JAMBI - Ahmad Fajar Rahmatullah; Ahmad Farhan Rahmatullah (Jurnal Ilmu Pemerintahan Widya Praja, 2021)
Good Governance is a new paradigm in the concept of Good Governance without exception in villages where this concept emphasizes three aspects, namely transparency, accountability, and participation. The Village Law clearly states that villages receive funds from the APBN which will later become a village fund program. Therefore, in this case, the Teluk Majelis Village Government in carrying out good village fund management must of course apply the three principles above. Using descriptive qualitative research methods. The results of the study found that the implementation of village fund management in Teluk Majelis village was in accordance with the concept of Good Governance.Keywords: Good Governance, Management, Village Fund, Teluk Majelis.